Effects Of Zinc Oxide Structures On Various Properties Of Zinc Oxide Eugenol Used In Dentistry - Bakhori, Siti Khadijah Mohd (2018)
The main objective of this thesis is to investigate effects of ZnO structure on various properties of zinc oxide eugenol (ZOE) used in dentistry. ZnO-A (rod shape), ZnO-B (plate shape), ZnO-Ax (oxygen annealed at 700 °C), and a commercial sample ZnO-K (multi-shape) represent four types of with different morphology zinc oxide (ZnO) powders. These ZnO powders were used to prepare different ZOEs labeled as ZOE-A, ZOE-B, ZOE-K, and ZOE-Ax. Streptococcus sobrinus and Streptococcus mutans were used to observe antibacterial activities in this study. Human gingival fibroblast (HGF) cell line was used for cytotoxicity test. Morphological, structural, and optical properties were characterized for all ZnO and ZOE samples. Electron microscopy revealed high contents of oxygen elements on particle surfaces of ZnO-Ax, followed by ZnO-A, ZnO-B, and ZnO-K. Distributed particle size from dynamic light scattering of ZnO-A measured 21.82 nm (91.9%), 52.21 nm (85.7%) for ZnO-B, 1140 nm for (100.0%) ZnO-K, and 20.08 nm (95.3%) for ZnO-Ax. Based on photoluminescence spectra, two peaks for all ZnO at ultraviolet (UV) and green luminescence (GL) regions were observed. However, intensity of the dominant peak at the UV region was extremely low in all ZOE compared with that in ZnO, and GL was almost diminished. Results imply loss of defects contained in each type of ZnO structures after mixing with eugenol because of hydrolysis. Antibacterial activities of all ZnO samples on S. sobrinus and S. mutans were studied at 0.5–2.0 mM. For S. sobrinus, inhibition percentages at 2.0 mM reached 82.32% (ZnO-A), 78.54% (ZnO-B), 55.30% (ZnO-K), and 89.0% (ZnO-Ax).